The Practice of Political Entrepreneurship in a Rural Javanese Village - Wawan Sobari (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This qualitative case study aims to explore the practice of political entrepreneurship in a rural Javanese village. Political entrepreneurship is dictated by the special interest of political entrepreneurs, incentives gained from the political system, and awareness about targeting the change of political institution, an explanation theorized by McCaﬀrey and Salerno (2011). Unlike the theory, this study assesses the importance of cultural explanation of political entrepreneurship which provides room in an academic discussion. The study reveals the role of Javanese (and Islam) values in encouraging the political entrepreneurship of a village head. Philosophical values of Javanese leadership promoting an exemplary leader (ing ngarso sung tulodo) and leadership behavior that is andap asor (humble) have favored public acceptance of the practice of political entrepreneurship. Furthermore, the doctrine (akhlak) and practices of Islamic rituals by the village head explain the direction of political entrepreneurship. This study discovers also the concept of ‘sungkan’ demonstrated in respect for the performance of the village head. Moreover, the ability to provide solutions to villagers’ problems practiced through suwuk and petungan add gratitude for the village head. Leadership behavior adhering to these cultural and religious values directly or indirectly induced a ‘sungkan’ eﬀect in a reelection bid (the 2013 Village Election). ‘Sungkan’, which is equal to electoral accountability, explicates the outcome of political entrepreneurship for the electoral process in the village that were relatively clean from vote-buying. Lastly, the casework expands political entrepreneurship theory, indeed, cultural and religious values can also drive the practice of political entrepreneurship.